Gender Biases in Resettlement Processes in Vietnam : Examining Women's Participation and Implications for Impact Assessment - Nghia, Nguyen Quy; Phuong, Nguyen Thi Minh; Hang, Do Thi Le (Taylor and Francis, 2021)
The impacts of development-induced resettlement disproportionately affect women, as they frequently face more difficulties than men to cope with disruption and changes. Women’s situation might further deteriorate if there is no mechanism for affected households to enjoy meaningful participation and consultation in the resettlement process. This paper is the result of policy analysis, project implementation experience, and findings of a cross-sectional survey of 876 affected households in Vietnam. We examine women's participation in resettlement processes in large infrastructure projects in Vietnam. The survey findings revealed the limited participation of women in the resettlement processes from all perspectives (meeting attendance, resettlement implementation, and making decisions) at community and household levels. Gender-stereotyped prejudice from community members and the gender-ascribed household division of labor were key factors inhibiting women’s meaningful participation. The paper also discusses the implications of the findings for impact assessment practice. We call for a shift in how resettlement is prepared and implemented towards a more comprehensive and gender-informed approach, with a view to making affected people genuine beneficiaries of resettlement programs.